Y=-2/5x+1/10=4x+10y=10
y=-3x=3x+y=0
hope these answers help
Answer:
Step-by-step explanation:
A perfect square trinomial is written as
, where
first term
= square of first term of binomial
second term=
=twice the product of both terms of binomial.
and third term 'c'=square of last term of binomial
Thus to create a perfect square trinomial put 'a' and 'c' a square number
Let a=4 and c=9
The required trinomial will be
![4x^2+12x+9](https://tex.z-dn.net/?f=4x%5E2%2B12x%2B9)
![=(2x)^2+2(2x)(3)+3^2\\=(2x+3)^2.......\text{[using pattern}(a+b)^2=a^2+2ab+b^2]\\=(2x+3)(2x+3)](https://tex.z-dn.net/?f=%3D%282x%29%5E2%2B2%282x%29%283%29%2B3%5E2%5C%5C%3D%282x%2B3%29%5E2.......%5Ctext%7B%5Busing%20pattern%7D%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2%5D%5C%5C%3D%282x%2B3%29%282x%2B3%29)
Answer:
![4x^{3}](https://tex.z-dn.net/?f=4x%5E%7B3%7D)
Step-by-step explanation:
<u>Given:</u>
![(\frac{192x^{12}}{3x^{3}} )^{\frac{1}{3}}](https://tex.z-dn.net/?f=%28%5Cfrac%7B192x%5E%7B12%7D%7D%7B3x%5E%7B3%7D%7D%20%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D)
<u>Apply exponent rule of distribution:</u>
![\frac{(192x^{12})^{\frac{1}{3}}}{(3x^{3})^{\frac{1}{3}}}](https://tex.z-dn.net/?f=%5Cfrac%7B%28192x%5E%7B12%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%7D%7B%283x%5E%7B3%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%7D)
<u>Simplify the numerator:</u>
![\\\\\frac{4 * 3^{\frac{1}{3}}x^{4}}{(3x^{3})^{\frac{1}{3}}}](https://tex.z-dn.net/?f=%5C%5C%5C%5C%5Cfrac%7B4%20%2A%203%5E%7B%5Cfrac%7B1%7D%7B3%7D%7Dx%5E%7B4%7D%7D%7B%283x%5E%7B3%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%7D)
<u>Simplify the denominator:</u>
![\\\frac{4 * 3^{\frac{1}{3}}x^{4}}{3^\frac{1}{3}x}}](https://tex.z-dn.net/?f=%5C%5C%5Cfrac%7B4%20%2A%203%5E%7B%5Cfrac%7B1%7D%7B3%7D%7Dx%5E%7B4%7D%7D%7B3%5E%5Cfrac%7B1%7D%7B3%7Dx%7D%7D)
<u>Simplify:</u>
![4x^{3}](https://tex.z-dn.net/?f=4x%5E%7B3%7D)
-> To explain this party since it is a bigger jump,
is on the top and the bottom, so it becomes a one. We are left with a four on the top, and using properties of exponents 4 - 1 = 3, explaining why we have
leftover too.
Have a nice day!
I hope this is what you are looking for, but if not - comment! I will edit and update my answer accordingly. (ノ^∇^)
- Heather
Answer:
3
lazy approach was with a graphic plotting program, but you can also calculate it. with the pq-formula.
p = -6
q = 9
x = -p/2 +- sqrt( (p/2)² - q)
x = -(-6)/2 +- sqrt ( (-6/2)² - 9)
x = 3 +- sqrt(9-9)
x = 3 +- sqrt(0)
x = 3 +- 0
x = 3